#### Answer

$\frac{n!}{(n-r)!(n-(n-r))!}=\frac{n!}{(n-r)!r!}$

#### Work Step by Step

The binomial coefficient of
$\binom{n}{r}=\frac{n!}{r!(n-r)!}$
Which equals to
$\binom{n}{n-r}=\frac{n!}{(n-r)!(n-(n-r))!}=\frac{n!}{(n-r)!r!}$

Published by
Pearson

ISBN 10:
0-32184-874-8

ISBN 13:
978-0-32184-874-1

$\frac{n!}{(n-r)!(n-(n-r))!}=\frac{n!}{(n-r)!r!}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.